A combined diagnostic model including middle rectal artery visualization for predicting lateral lymph node metastasis in rectal cancer - Wang, Ning; Li, Yiping; Lu, Kun; Wei, Kaikai; Jia, Shize; Fan, Shuhong; Ren, Donglin; Fu, Yuanji; Liu, Zhimin (Frontiers in Physiology, 2025)
PurposeThis study attempted to establish a combined diagnostic model encompassing visualization of the middle rectal artery (MRA) and other imaging features to improve the diagnostic efficiency of lateral lymph node (LLN) metastasis, which is crucial for clinical decision-making in rectal cancer.MethodOne hundred eleven patients receiving bilateral or unilateral lymph node dissection were enrolled, and 140 cases of LLN status on a certain unilateral pelvic sidewall were selected. Enhanced computed tomography (CT) was used to determine whether MRA was visible. Multivariable regression was used to establish a diagnostic model combining MRA visualization with other imaging features to predict LLN metastasis. Receiver operating characteristic (ROC) curve and area under the ROC curve (AUC) were used to test the diagnostic efficacy for LLN metastasis. Ten-fold cross-validation was completed to internally validate the diagnostic model.ResultsOf the 140 LLNs harvested from 111 patients, 76 were positive and 64 were negative for metastases, respectively. The diagnostic model combining the MRA visualization and lymph node short diameter showed a greater efficiency than a single scale (AUC = 0.945, 95% confidence interval = 0.893–0.976, P < 0.001). The mean cross-validated AUC was 0.869 (95% confidence interval = 0.835–0.903).ConclusionOur results establish a combined diagnostic model with the help of MRA visualization to yield a high diagnostic efficiency of LLN metastasis in rectal cancer.